2017
DOI: 10.1080/23789689.2017.1345257
|View full text |Cite
|
Sign up to set email alerts
|

Resilience analysis: a mathematical formulation to model resilience of engineering systems

Abstract: Resilience of engineering systems is related to their ability of absorbing both gradual and abrupt changes under exposure conditions and rapidly recover from disruptions. In this thesis, we develop a general stochastic formulation to model the recovery process and quantify system's resilience. In particular, we develop models for time-dependent capacity of a system and the imposed demand, under joint effects of recovery and shock deterioration processes. Using the developed models, a recovery curve is formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 199 publications
(68 citation statements)
references
References 45 publications
0
68
0
Order By: Relevance
“…They not only contribute – through cascading effects – to widespread failure propagation, but also to the smoothness or difficulty of the entire recovery process. The recovery rate of system components depends upon several factors that are often difficult to understand, model, and predict, as for example the recovery strategy and the amount, rate and prioritization of resource mobilization (Bruneau et al, 2003; Franchin & Cavalieri, 2015; Jia et al, 2016; Sharma et al, 2016). It may be impractical and unnecessary to model every infrastructure system within a community fully capturing every physical and societal factors during the recovery.…”
Section: Modeling Of Network Dependenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…They not only contribute – through cascading effects – to widespread failure propagation, but also to the smoothness or difficulty of the entire recovery process. The recovery rate of system components depends upon several factors that are often difficult to understand, model, and predict, as for example the recovery strategy and the amount, rate and prioritization of resource mobilization (Bruneau et al, 2003; Franchin & Cavalieri, 2015; Jia et al, 2016; Sharma et al, 2016). It may be impractical and unnecessary to model every infrastructure system within a community fully capturing every physical and societal factors during the recovery.…”
Section: Modeling Of Network Dependenciesmentioning
confidence: 99%
“…Examples of restoration functions can be found in the literature either postulated (e.g. Ayyub, 2014; Bocchini et al, 2012; Cimellaro et al, 2010; Titi et al, 2015) or derived based on more fundamental recovery activities (Sharma et al, 2016). The state of system damage, functionality, and operational values is updated and used for the next time step, taking into account interand intra-system dependencies.…”
Section: Assessing the Resilience Of Dependent Critical Infrastrucmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that seismic degradation significantly increases structures' vulnerability. Recent progress in life cycle analysis and resilience analysis confirm these results . Zhai et al investigated the input energy spectra of main shock‐aftershock (MS‐AS) sequences for inelastic single‐degree‐of‐freedom (SDOF) systems and concluded that the effects of aftershocks on the input energy are significant in almost the whole period region.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in life cycle analysis and resilience analysis confirm these results. [14][15][16][17][18] Zhai et al 19 investigated the input energy spectra of main shock-aftershock (MS-AS) sequences for inelastic single-degree-of-freedom (SDOF) systems and concluded that the effects of aftershocks on the input energy are significant in almost the whole period region. Therefore, over time, structures can be progressively damaged by aftershocks, which leads to a higher probability of structural failure than when considering the main shock only.…”
mentioning
confidence: 99%